Arm coordination in elite bachstroke swimmers - Carter, M.; Seifert, L.; Chollet, D. (First international symposium sciences and practices in swimming, 2006)
Based on an adaptation of the index of coordination (Chollet et al., 2000) used in front crawl, the aim of this study was to assess the elite backstroke swimmers arm coordination according to their spatial-temporal parameters. Fourteen elite backstroke swimmers (89.5% of the world record) performed four race paces; then the backstroke arm movement was divided into six phases. Unlike in front crawl where three coordination modes were observed (catch-up, Opposition, superposition), arm coordination in backstroke was always in catch-up because the shoulder anatomic constraints and the Clearing phase did not allow continuity or overlap of the propulsive phases.